(untitled) (Global Journal of Human-Social Science, 2025)
This article examines the protection afforded to migrants asylum seekers and refugees under Article 3 of the European Convention on Human Rights which prohibits torture inhuman or degrading treatment or punishment Triggered by the refugee crisis in recent years migration to Europe has led to increased border securitization and reports of ill-treatment by state authorities The paper explains how Article 3 has been applied by the European Court of Human Rights in such contexts evaluates its implementation and identifies key obstacles to its effective enforcement Recommendations are also offered to strengthen the protection framework within Council of Europe states